The Relationship between self-efficacy in implementing diet with the blood sugar levels in DM patients in the working area of the Bara-baraya community health center at Makassar City. - sri angriani; Raodatul Jannah; Agusti Fauziah (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2020)
Background: Self-efficacy in implementing diets in patients with diabetes mellitus focuses on the patient's believeness in being able to do the behaviors that can support the improvement of their illness and the improve the management of his self-care. Low self-efficacy will have an impact on decreasing the self-care of diabetic patients in complying with various factors such as unstable blood sugar levels. Research Objectives: To know the relationship between self-efficacy in the implementation of the diet with blood sugar levels in DM patients in the working area of the Bara-Baraya Public Community Health Center at Makassar city. Research Methods: this research used a cross sectional approach. The sample of this research was 50 diabetic patients. Random sampling technique. The data analysis includes of univariate and bivariate using the chi square test. Research Results: Based on statistical tests, it found that a significant relationship between self-efficacy in the implementation of the diet with blood sugar levels (p value: 0,000). The conclusion: There is a relationship between self-efficacy in the implementation of diet with blood sugar levels in DM patients in the Bara-Baraya Public Community Health Center at Makassar city.